Maximizing the value of trade wastes - Berzal de frutos, Olivia (Cranfield University, 2018)
Poster presented at the Cranfield Doctoral Network Annual Event 2018.Anaerobic digestion (AD) is the use of microorganism in the absence of oxygen to degrade organic compounds. AD is commonly used to treat highly concentrated wastes, such as waste sludge from municipal wastewater treatment plants. Similar, trade wastes (TWs), wastewaters generated from industrial or production processes, known to contain high levels of organics as compared to domestic wastewater, are often treated in anaerobic systems. The treatment of sludge in AD has been seen to be enhanced with the addition of TWs. However, as any biological system, the bacteria may be affected by toxic compounds present in the substrate, and TWs are a potential source of compounds affecting anaerobic bacteria with, for instance, ammonia, heavy metals, and fats oils and greases. Therefore, there is a need to understand the possible impact of those compounds in AD of TWs and sludge. This research aims to understand the limitations and benefits of using TWs in anaerobic digesters treating wastewater sludge and in particular the impact TWs may have on biogas production and stability of the reactors. The impacts of using TWs on the AD of sludge were assessed in this project by testing controlled addition of the compounds of interest in batch reactors treating sludge. This data will be compared to the characteristics of TWs to select them for further experiments. The final result will be a decision support tool that could be used for water companies to decide the TWs to be added to the digester.
Keywords: anaerobic digestion'; 'sludge'; 'trade waste'; 'CranfieldDN2018'; 'Wastewater Treatment Processes'